2019
DOI: 10.1002/2211-5463.12676
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long noncoding RNA MALAT1 promotes the stemness of esophageal squamous cell carcinoma by enhancing YAP transcriptional activity

Abstract: The tumor promoting roles of long noncoding RNA (lncRNA) MALAT1 have been revealed in various cancers; however, its roles in esophageal squamous cell carcinoma (ESCC) have not previously been disclosed. In this study, we found that MALAT1 expression was remarkably increased in ESCC cells compared to normal human esophageal epithelial cells. In addition, knockdown of MALAT1 attenuated the stemness of ESCC cells, as evidenced by a decrease in spheroid formation capacity, stemness marker expression and aldehyde d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Hepatic CSCs are a small sub-population of undifferentiated cancerous liver cells, implicated as drivers of cancer initiation, metastasis, resistance to therapy, and disease recurrence; these HCC-SCs pool is enriched for and isolated based on the cell functions attributable mainly to side population (SP), enhanced ALDH activity and auto-fluorescence, as well as immunophenotypes defined by the cell surface CD13, CD24, CD44, CD47, CD90, CD133, DLK1, EpCAM, or ICAM-1 proteins [26], therefore the our demonstrated ability of MALAT1 to modulate the expression of ALDH and CD133 with their associated stemness phenotypes is not only relevant in understanding the pathobiology of HCC, but also therapeutically significant. The present finding is consistent with a previous finding by our team indicating that MALAT1 overexpression with correlated aberration in KDM5B/hsa-miR-448 ratio promotes breast cancer aggressiveness and stemness [27], as well as with others indicating MALAT1 promotes stemness in esophageal squamous cell carcinoma [28] and gastric cancer [29].…”
Section: Discussionsupporting
confidence: 93%
“…Hepatic CSCs are a small sub-population of undifferentiated cancerous liver cells, implicated as drivers of cancer initiation, metastasis, resistance to therapy, and disease recurrence; these HCC-SCs pool is enriched for and isolated based on the cell functions attributable mainly to side population (SP), enhanced ALDH activity and auto-fluorescence, as well as immunophenotypes defined by the cell surface CD13, CD24, CD44, CD47, CD90, CD133, DLK1, EpCAM, or ICAM-1 proteins [26], therefore the our demonstrated ability of MALAT1 to modulate the expression of ALDH and CD133 with their associated stemness phenotypes is not only relevant in understanding the pathobiology of HCC, but also therapeutically significant. The present finding is consistent with a previous finding by our team indicating that MALAT1 overexpression with correlated aberration in KDM5B/hsa-miR-448 ratio promotes breast cancer aggressiveness and stemness [27], as well as with others indicating MALAT1 promotes stemness in esophageal squamous cell carcinoma [28] and gastric cancer [29].…”
Section: Discussionsupporting
confidence: 93%
“…BCA Protein Quantification Kit (Tiangen, Beijing, China) was used to measure the protein concentration. Then the detailed procedure was performed following the protocols mentioned in the previous work [13]. The antibody information was listed as below: CD133 (cat # 66666-1-Ig, 1: 1000, Proteintech, Wuhan, China), CD44 (Cat # 15675-1-AP, 1: 1000, Proteintech), b-actin (Cat # 66009-1-Ig, 1: 1000, Proteintech), RNPC1 (Cat # ab200403, 1: 3000, Abcam, Cambridge, MA, USA), MST1 (Cat # ab232551, 1: 3000, Abcam), MST2 (Cat # ab23232, 1: 2000, Abcam), LATS1 (Cat # ab70561, 1: 3000, Abcam), LATS2 (Cat # ab110780, 1: 3000, Abcam), p-LATS1 (Cat # 9157S, 1: 1500, Cell Signaling Technology, Danvers, MA, USA) and p-LATS2 (Cat # RY-K4082, 1: 500, Shanghai Runyu, Shanghai, China).…”
Section: Western Blotmentioning
confidence: 99%
“…Recent works showed that lncRNAs are associated with YAP activity, such as lncRNA B4GALT1-AS1 [ 17 , 18 ], lncRNA TUG1 [ 19 ], and lncRNA THOR [ 20 ], in which YAP transcriptional activity is responsible for lncRNA-mediated regulation on cell stemness; these effects supporting the promoting role of YAP in tumor cell stemness [ 21 , 22 ]. Moreover, it is indicated that MALAT1 induces YAP activity contributing to the stemness-related traits of esophageal squamous cell carcinoma [ 23 ]. We wondered whether YAP is essential for MALAT1-induced effects on OC cell stemness.…”
Section: Introductionmentioning
confidence: 99%